Synthesis of tin(IV) complexes of chlorophyll-a derivatives with two halides as axial ligands and their optical properties in solution. Issue 8 (21st February 2020) - Kawamoto, Yuki; Kinoshita, Yusuke; Tamiaki, Hitoshi
Abstract: Methyl pyropheophorbides prepared from naturally occurring chlorophyll- a were reacted with tin(II) dihalide in aerated solvents to give their tin(IV) complexes with two halides as the axial ligands. The tin(II)-insertion into the central position and the successive air-oxidation of tin(II) to tin(IV) proceeded cleanly for the 3-ethyl-, vinyl-, acetyl-, and formyl-chlorins. Their visible absorption and fluorescence emission maxima in dichloromethane were shifted to longer wavelengths in the order of F < Cl < Br as the axial ligand and CH2 CH3 < CH = CH2 < COCH3 < CHO as the 3-substituent. The heavy atom effect was observed for their fluorescence emission quantum yields and lifetimes, which were suppressed in the order of H2 (free base) > SnF2 > SnCl2 > SnBr2 at the central position. Graphical abstract: Image 1 Highlights: Tin-metalated chlorophyll- a derivatives with two axial halide ligands were prepared. The synthetic tin(IV) complexes were characterized by 1 H/ 19 F NMR and mass spectra. The diastereomeric α- and β-ligated fluorides were discriminated in CDCl3 by 19 F NMR. The absorption and emission maxima in CH2 Cl2 were red-shifted in F < Cl < Br ligands. Heavy atom effect was visible for fluorescence emission quantum yields and lifetimes.